Analisis Penerapan Keselamatan Kerja Pada Petugas Laboratorium Klinik di Kota Pekanbaru - Ismulyati Ismulyati; Rahman Karnila; Elda Nazriati (Universitas Riau, 2016)
Abstrak: The workers in clinical laboratories were suspected to always threatened a number of risks and potential accidents due to the interaction between the labor, equipment, materials and labor and environmental situation in it. In addition, the lack of understanding and awareness of companies/agencies and workers to anticipated and managed the potential risks in the laboratory in accordance with established standards. Research has been conducted in nine private clinical laboratories from February to December 2014 with 39 respondents of laboratory workers. This research was a quantitative study which using observational design. Data collection techniques in this research was using interviews, direct observation and questionnaires which distributed to the management of clinical laboratory and clinical laboratory workers. The quality of the clinical laboratory in Pekanbaru city of fair quality were three of eight laboratories. The results of clinical laboratory management signified the majority of fair quality that five of the eight laboratories in Pekanbaru city. The results of behavioral assessment of clinical laboratory workers were not well behaved. Measurement of behavior consists of knowledge attitude and practice of clinical laboratory workers. The measurement results of clinical laboratory workers were moderate categorized, nice attitudes, but the practice was not well categorized.